2019
DOI: 10.1002/aenm.201803480
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Pseudocapacitive Contribution in Nanocage‐Shaped Silicon–Carbon Composite Anode

Abstract: Pseudocapacitive materials have been highlighted as promising electrode materials to overcome slow diffusion‐limited redox mechanism in active materials, which impedes fast charging/discharging in energy storage devices. However, previously reported pseudocapacitive properties have been rarely used in lithium‐ion batteries (LIBs) and evaluation methods have been limited to those focused on thin‐film‐type electrodes. Hence, a nanocage‐shaped silicon–carbon composite anode is proposed with excellent pseudocapaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 40 publications
0
53
0
Order By: Relevance
“…More seriously, repeated huge volume change during cycling can bring about structural degradation and increased space between particles as factors related to losing contact between particles and accelerating electrode swelling, resulting in electrical isolation and low volumetric capacity, respectively . Thus, for the successful implementation of G‐Si system into advanced LIBs, the rational distribution of high Si content in the composite anode is a must to accommodate Si volume expansion . Previously, we reported that volume expansion of Si in G‐Si system can be accommodated via selectively located Si in macropore of mesopore‐degenerated G .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More seriously, repeated huge volume change during cycling can bring about structural degradation and increased space between particles as factors related to losing contact between particles and accelerating electrode swelling, resulting in electrical isolation and low volumetric capacity, respectively . Thus, for the successful implementation of G‐Si system into advanced LIBs, the rational distribution of high Si content in the composite anode is a must to accommodate Si volume expansion . Previously, we reported that volume expansion of Si in G‐Si system can be accommodated via selectively located Si in macropore of mesopore‐degenerated G .…”
mentioning
confidence: 99%
“…However, when applied power density was increasing over 3000 W kg −1 , EGS (220 Wh kg −1 at 6000 W kg −1 ) exhibited an outstanding gravimetric energy density than that of HGS (153 Wh kg −1 ) and B‐Si (127 Wh kg −1 ). This result can be ascribed to the benefits of EGS design, which has widely distributed thin Si layers together with significant void space …”
mentioning
confidence: 99%
“…[25,26] In addition to the XRD analysis, we further performed Raman spectroscopy analysis. More specifically, the cubic ZnS crystal structure can also be confirmed by the observation of the exposed (220) and (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) crystal planes along the zone axis of [001], as indicated by d-spacings of lattice fringes in Figure 1f. The morphology of the ZnSi 2 P 3 powder was further examined using field-emission scanning electron microscopy (FESEM; Figure S1, Supporting Information) and low-magnitude transmission electron microscopy (TEM, Figure 1e).…”
Section: Synthesis and Structural Characterizations Of Znsi 2 Pmentioning
confidence: 69%
“…As shown in Figure 4e, the Coulombic efficiency remains at ≈100% after 500 cycles at a current density of 300 mA g −1 while maintaining ≈80.5% of the initial discharge capacity (at 1955 mAh g −1 ). Notably, the Li-storage performance of the ZnSi 2 P 3 /C nanocomposite is superior to most reported P-and Si-based anodes [2,3,6,8,9,11,19,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] in terms of initial Coulombic efficiency and cycling stability (Figure 4g). Notably, the Li-storage performance of the ZnSi 2 P 3 /C nanocomposite is superior to most reported P-and Si-based anodes [2,3,6,8,9,11,19,[32][33][34][35][36][37][38][39][40][41][42][43]…”
Section: Li-storage Performance Of Znsi 2 P 3 /C Nanocompositementioning
confidence: 85%
See 1 more Smart Citation